2018
DOI: 10.18203/2319-2003.ijbcp20181632
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization pattern in pregnancy at a tertiary care hospital in Puducherry: a cross sectional observational study

Abstract: Background: Drug utilization pattern in pregnancy population provide insights regarding drug profile and interventional measures and also minimizes the inherent risk occurring due to unethical prescription.Methods: It was a prospective cross sectional study where prescription slips were collected. Further drugs were categorized according to the classification defined by US Food and drug Administration for pregnancy. Using Pre validated questionnaire the pregnant women were interviewed and parameters regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
1
1
Order By: Relevance
“…However, the use of medications is sometimes mandatory in the treatment of women of reproductive age, breast feeding and during pregnancy. 21 In our study a total of 168 participants were interviewed; of whom, 81(51.9%) patients were age between 20-35 years were higher than consistent with the study done at a tertiary care hospital in Puducherry 22 which revealed among 365 pregnant women attending antenatal clinic, 43% were in age group of 22 to 25 years which represents the normal reproductive age group. This difference was due to participants age classification category.…”
Section: Discussionsupporting
confidence: 66%
“…However, the use of medications is sometimes mandatory in the treatment of women of reproductive age, breast feeding and during pregnancy. 21 In our study a total of 168 participants were interviewed; of whom, 81(51.9%) patients were age between 20-35 years were higher than consistent with the study done at a tertiary care hospital in Puducherry 22 which revealed among 365 pregnant women attending antenatal clinic, 43% were in age group of 22 to 25 years which represents the normal reproductive age group. This difference was due to participants age classification category.…”
Section: Discussionsupporting
confidence: 66%
“…Whereas, results of study conducted in Puducherry showed that 3.6% of third trimester women were prescribed with category B drugs. 25 In the current study, category D drugs were prescribed in 1.05% of pregnant women whereas higher prevalence of prescription (9.3%) of category D drugs was reported in other study in Ethiopia. 26 Results of the current study showed that diclofenac belonged to category D and C in 1.78% and 4.2% of cases respectively.…”
Section: Discussioncontrasting
confidence: 58%
“…Similar kind of results were found in our study population i.e., 15.7 % of prescriptions were of folic acid. In another study conducted by Selvaraj et al [12] the most commonly prescribed drugs in 1 st , 2 nd , and 3 rd trimester were iron, calcium and folic acid which we can see in our results too i.e., 15.2 % calcium and 7.1 % ferrous fumarate were prescribed.…”
Section: Table 3: Ddd/100 Bed D Of Fda Category Drugs (A and B) Used ...supporting
confidence: 67%